Crithmum maritimum L.—Study on the Histochemical Localization of Essential Oil - Velina Dzhoglova; Kalin Ivanov; Niko Benbassat; Yoana Georgieva-Dimova; Rayna Ardasheva; Diana Karcheva-Bahchevanska; Stanislava Ivanova (Plants, 2024)
Crithmum maritimum L. is a perennial halophyte plant that is a medicinal herb known by people from different cultures since ancient times. However, the therapeutic potential of this halophyte has not been completely investigated, and the scientific data on it are limited. The purpose of the present study was to estimate the chemical composition of the essential oil (EO) obtained from the aerial parts of Crithmum maritimum L. growing wild in Bulgaria, as well as the histolocalization of secretory structures for the synthesis and accumulation of volatile oils. The results obtained on the EO composition of Bulgarian Crithmum maritimum L. provide an opportunity to reveal potential future applications in various fields, such as medicine, pharmacy, agriculture, food, and the cosmetic industry. Gas chromatography with mass spectrometry was performed to assess the chemical profile of the isolated EO. The phenylpropanoid dillapiole was identified as the major compound in the EO, accounting for 34.09% of the total EO. Monoterpene hydrocarbons represented 62.07% of the total oil composition. γ-Terpinene, D-limonene, and β-pinene were the most abundant monoterpene hydrocarbons in the composition of the EO. In addition, histochemical localization of EO in the stem and leaves of Crithmum maritimum L. was carried out. The secretory structures were located in the cortical region of the stem and in the mesophyll tissues of the leaves in the form of secretory ducts. The performed histochemical analysis confirmed the lipophilic nature of the secretion from the duct cells. This is the first report related to the histolocalization and chemical composition of the EO from Bulgarian Crithmum maritimum L. Furthermore, our data indicate some potential possibilities for the evaluation of the therapeutic activity of the EO obtained from this plant species and outline its future applications as a therapeutic agent. Also, the EO from the studied halophyte plant has prominent potential to be used as a biopesticide, which is an environmentally friendly option compared to standard pesticides.